Agathokles und Hieron II. Zwei basileis in hellenistischer Zeit und die Frage ihrer Nachfolge - Haake, Matthias (Gerión. Revista de Historia Antigua, 2006)
The aim of this contribution is to analyze an aspect of the reigns of Agathocles and Hiero II of Syracuse, namely, the question of succession in their monarchic position. The contribution starts with an outline of how the two kings organized their respective succession. Then, explanations are suggested for the different arrangements adopted by the two of them. Finally, the contribution addresses the question of why Agathocles and Hiero failed in their project of creating a dynasty by establishing a successor.